2022
DOI: 10.1155/2022/9295627
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical Analysis on the Effects of Tandospirone Citrate Assisted by Drawing Therapy on Medication Compliance and Sleep Quality in Patients with Anxiety Disorders

Abstract: Objective. To explore the clinical effects of tandospirone citrate assisted by drawing therapy (DT) on medication compliance and sleep quality in patients with anxiety disorders. Methods. A total of 128 patients with anxiety disorders treated in the hospital were enrolled between January 2020 and January 2022. According to the random number table method, they were divided into the observation group (n = 64) and the control group (n = 64). The control group was treated with tandospirone citrate, while the obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…To combat the debilitating consequences of sleep disorders, a plethora of pharmacologic treatments have been introduced to the market and prescribed by physicians [20][21][22][23][24][25][26]. While medications have shown efficacy in decreasing sleep latency, significant side effects have been associated with these medications [27][28][29][30][31][32]. These include addiction, respiratory depression, decreased quality of sleep, and significant withdrawal symptoms when these medications are discontinued [21,[33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…To combat the debilitating consequences of sleep disorders, a plethora of pharmacologic treatments have been introduced to the market and prescribed by physicians [20][21][22][23][24][25][26]. While medications have shown efficacy in decreasing sleep latency, significant side effects have been associated with these medications [27][28][29][30][31][32]. These include addiction, respiratory depression, decreased quality of sleep, and significant withdrawal symptoms when these medications are discontinued [21,[33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…This form of creative self-expression is believed to contribute to stress reduction, enhanced emotional regulation, improved self-awareness, and inner balance [5] . Painting therapy has been widely applied in the treatment of various psychological issues, including anxiety disorders, depression, post-traumatic stress disorder, and self-esteem problems [6,7,8] . However, traditional painting therapy still faces several challenges.…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Manipulated or compromised peer review …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%